2021
DOI: 10.31234/osf.io/bpjnu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond Description and Deficits: How Computational Psychiatry Can Enhance an Understanding of Decision-Making in Anorexia Nervosa

Abstract: Despite decades of research, anorexia nervosa (AN) remains poorly understood and clearly effective treatments continue to be elusive. Thus, novel theoretical frameworks are needed to advance mechanistic and treatment research for this disorder. Progress in research on AN may have been slowed by systematic biases historically affecting psychiatric research. In this manuscript, we describe the influence of two such biases: 1) Descriptive bias: the tendency to define mechanisms on the basis of surface or face-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 111 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…Similarly, adults with BED and obesity showed greater exploration than adults with obesity only on a clock task, wherein participants selected when to stop the clock to obtain an unknown reward (Morris et al, 2016), and more switching (exploratory) behavior than non‐ED controls on a reward‐based decision‐making task (Reiter et al, 2017). In contrast, preliminary evidence suggested that adults with AN are more exploitative than non‐ED controls in a cross‐species foraging task (Haynos, 2021).…”
Section: Understanding Eds Through Explore/exploit Decision‐makingmentioning
confidence: 99%
“…Similarly, adults with BED and obesity showed greater exploration than adults with obesity only on a clock task, wherein participants selected when to stop the clock to obtain an unknown reward (Morris et al, 2016), and more switching (exploratory) behavior than non‐ED controls on a reward‐based decision‐making task (Reiter et al, 2017). In contrast, preliminary evidence suggested that adults with AN are more exploitative than non‐ED controls in a cross‐species foraging task (Haynos, 2021).…”
Section: Understanding Eds Through Explore/exploit Decision‐makingmentioning
confidence: 99%